Speaker Accent Modulates the Effects of Orthographic and Phonological Similarity on Auditory Processing by Learners of English - Frances, Candice; Navarra-Barindelli, Eugenia; Martin, Clara D. (Frontiers in Psychology, 2022)
The cognate effect refers to translation equivalents with similar form between languages—i.e., cognates, such as ‘band’ (English) and ‘banda’ (Spanish)—being processed faster than words with dissimilar forms—such as, ‘cloud’ and ‘nube’. Substantive literature supports this claim, but is mostly based on orthographic similarity and tested in the visual modality. In a previous study, we found an inhibitory orthographic similarity effect in the auditory modality—i.e., greater orthographic similarity led to slower response times and reduced accuracy. The aim of the present study is to explain this effect. In doing so, we explore the role of the speaker’s accent in auditory word recognition and whether native accents lead to a mismatch between the participants’ phonological representation and the stimulus. Participants carried out a lexical decision task and a typing task in which they spelled out the word they heard. Words were produced by two speakers: one with a native English accent (Standard American) and the other with a non-native accent matching that of the participants (native Spanish speaker from Spain). We manipulated orthographic and phonological similarity orthogonally and found that accent did have some effect on both response time and accuracy as well as modulating the effects of similarity. Overall, the non-native accent improved performance, but it did not fully explain why high orthographic similarity items show an inhibitory effect in the auditory modality. Theoretical implications and future directions are discussed.